Analysis of junior tennis development at azwa tennis academy (ata): a cipp model evaluation - Ninik Purnaningsih; Ruslan Ruslan; Suriyadi Datau (Jambura Arena Sport, 2026)
Junior athlete development is a primary determinant of achievement in competitive tennis, yet the effectiveness of privately managed academies in Indonesia has rarely been examined using a comprehensive program-evaluation framework. This study analyzed the junior tennis development program at Azwa Tennis Academy (ATA), the first tennis academy in Gorontalo Province, using Stufflebeam's Context, Input, Process, and Product (CIPP) evaluation model. A mixed-methods design combined a Likert-scale questionnaire with observation, interviews, and documentation, involving the entire population of 34 stakeholders (15 athletes, 4 coaches, 10 parents, and 5 management staff) selected through total sampling. Quantitative data were analyzed descriptively using mean scores and percentage distribution, while qualitative data from interviews and observation were used to substantiate the numerical findings. The results show that 70.6% of respondents rated the context component as very good, reflecting a clear alignment between the academy's objectives and its developmental program; 70.6% rated the input component as very good, supported by adequate athletes, coaches, and facilities despite a shortage of training balls; 55.9% rated the process component as good, characterized by regular but short-term, weekly-structured training; and 61.8% rated the product component as very good, evidenced by athletes' achievements in regional and inter-regional tournaments, although national-level achievement has not yet been attained. The novelty of this study lies in applying the CIPP model to an independently managed, non-government-affiliated sports club, showing that community-based academies can achieve strong contextual and product outcomes despite limited institutional supervision. The findings imply that ATA's sustainability depends on developing a structured long-term training program, diversifying training methods, and strengthening facility support and government partnership.